Sistem Manajemen Arsip Dinamis di Perpustakaan Politeknik Negeri Manado - Jufrina Mandulangi; Juliet P.T. Makinggung; Sonny Kasenda; Frans Luntungan (Prosiding Seminar Nasional Produk Terapan Unggulan Vokasi, 2022)
The main problem raised in this study is how dynamic archive management at the Manado State Polytechnic library is regarding the inhibiting factors in the dynamic archive management system in the library. The purpose of this research is to find out how the dynamic records management system is applied in order to find out the inhibiting factors in the dynamic records management system in the library. The type of research used is descriptive qualitative type. The method applied in this study is a qualitative approach. The instruments used were the researchers themselves and the team as internal members using tools in the form of observation, interview guides and documentation. The data analysis technique used was descriptive qualitative data analysis technique. The results of the study show that the dynamic records management system in the library uses a control card system, with the principle of organizing archives using a combination of centralization and decentralization as well as management or management of active and inactive dynamic archives in the library, namely: starting from creating archives in managing incoming and outgoing mail, filing and dynamic archive management and depreciation, active dynamic archive transfer and archive destruction. As for the inhibiting factors found, there is still a lack of human resources or manpower, it is necessary to add infrastructure and add systems from manual to computerized systems.